Cultural Identity in Contemporary Children’s Literature: A Jungian Archetypal Analysis of A Lucky Chinese New Year - Sharenlie, Grania; Chang, Gabrielle Angela; Djohan, Febrina Stevani; Surya, Michaella Isabel; Maradona, Amadea Krista; Widjaya, Yemima Candice (Jurnal Pendidikan Makarios, 2024)
This research investigates how archetypes within children's literature not only reinforce cultural traditions and values in collective unconsciousness of individuals, but also emphasize the role of family unity and generational continuity in maintaining cultural heritage in a modern, globalized context in the preservation of cultural identity within the children's book "A Lucky Chinese New Year." By analyzing the Hero, Child, and Caregiver archetypes as embodied by the characters, the primary Jungian theory used in the analysis is Carl Jung's Archetypal Theory (1959), particularly focusing on the collective unconscious and universal archetypes. Meanwhile, Confucianism theory by Tu Weiming (1985) was used as the secondary theory to discuss cultural context. The study reveals how these archetypes support the themes of cultural preservation, renewal, and family unity. As the results: 1) Lily's actions embody the Hero's journey, demonstrating how even small actions by young individuals can significantly contribute to maintaining cultural traditions; This reinforces the idea that cultural preservation is a collective effort that transcends age. 2) The Child archetype in Lily symbolizes new beginnings and the continuity of cultural practices across generations, emphasizing the role of the younger generation in sustaining and revitalizing traditions and reflecting a cyclical pattern of cultural renewal. 3) The Caregiver archetype, embodied by Lily's family, highlights the importance of family support in upholding and transmitting cultural heritage. Together, these archetypes illustrate the interconnectedness of individual and collective efforts in creating narratives with similar themes to ensure the cultural traditions are preserved and passed down to future generations; this demonstrates the powerful role of children's literature in cultural preservation.